PHARMACOLOGICAL INVESTIGATION OF THE ORAL WOUND HEALING ACTIVITY OF Stachytarpheta jamaicensis ROOT EXTRACT GEL IN WISTAR RATS - Utami, Juliyatin Putri; Wasiaturrahmah, Yusrinie; Carabelly, Amy Nindia; Aspriyanto, Didit; Nahzi, Yanuar Ichrom; Arifin, Rahmad; Ramadhaniyah, Nur; Jatmiko, Habibi Naufal (BRIN - Badan Riset dan Inovasi Nasional, 2025)
The Stachytarpheta jamaicensis (L) Vahl root contains bioactive compounds like saponins, alkaloids, flavonoids, tannins, phenols, and terpenoids, which have antibacterial and anti-inflammatory properties. This study investigates the wound healing effects of Stachytarpheta jamaicensis (L) Vahl root extract gel in oral mucosa. The experiment involved 28 male Wistar rats, divided into four groups: a positive control treated with povidone iodine 10%, a negative control treated with gel base, and two experimental groups treated with 6% and 10% S. jamaicensis root extract gels. The gel was applied twice daily, and wound healing was assessed by epithelial thickness, inflammation cell and hydroxyproline content. Both concentrations of S. jamaicensis root extract gel significantly enhanced wound healing, as shown by increased epithelial thickness, inflammation cell and hydroxyproline content levels compared to the negative control. These findings suggest that S. jamaicensis root extract gel effectively promotes wound healing in the excision wound model.